Three-Dimensional Human Modeling Applications in Sport Sciences - Mehmet İmamoğlu; Osman İmamoğlu (Türk Spor ve Egzersiz Dergisi)
The purpose of this study is to examine three-dimensional human modeling software suitable for use in the field of sport sciences.